2017
DOI: 10.17221/243/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of PCR-RFLP and species-specific PCR for the identification of meat origin in dry sausages

Abstract: Djurkin Kušec I., Samac D., Margeta V., Radišić Ž., Vincek D., Kušec G. (2017): Efficiency of PCR-RFLP and species-specific PCR for the identification of meat origin in dry sausages. Czech J. Food Sci., 35: 386-391.The purpose of this investigation was the identification of chicken, beef and sheep meat in pork sausages using PCR-RFLP and PCR with species-specific primers. Six dry fermented pork sausages were produced by adding beef, sheep and chicken meat to each in the amount of 1 and 5%. DNA was extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…The extreme sensitivity of the real time PCR technique is mentioned in the literature [ 3 , 15 , 16 ]. However, it was also reported that the mixing distributes the ingredients through the sausage in an unpredictable manner [ 17 ]. Thus, addition or cross contamination of small amounts of chicken meat might not be distributed thoroughly in sausages.…”
Section: Resultsmentioning
confidence: 99%
“…The extreme sensitivity of the real time PCR technique is mentioned in the literature [ 3 , 15 , 16 ]. However, it was also reported that the mixing distributes the ingredients through the sausage in an unpredictable manner [ 17 ]. Thus, addition or cross contamination of small amounts of chicken meat might not be distributed thoroughly in sausages.…”
Section: Resultsmentioning
confidence: 99%
“…The AuNPs were conjugated with specific oligonucleotides for cow mitochondrial DNA: sense primer GCCATATACTCTCCTTGGTGACA and antisense primer GTAGGCTTGGGAATAGTACGA (Invitrogen™, USA). The oligonucleotides were modified with 10xdATP in the 5′-end of the primer and thiolated (Cheng et al, 2006;Lahiff et al, 2001;Kusec et al, 2017). The AuNPs were conjugated with the oligonucleotides by adding 1 ml of AuNPs into 4 nmol of the oligonucleotides using a previously described protocol by Hill and Mirkin (2006).…”
Section: Preparation Of Gold Nanoparticle Probesmentioning
confidence: 99%
“…55 The same results observed in domestic animals using PCR-RFLP were obtained in assessing the possible adulteration of sausage products made with chicken. 56 Moreover, PCR-RFLP has also been considered in the study of some growth and performance traits. 57 However, PCR-SSCP was considered as a cornerstone in recent post-PCR genotyping studies on poultry, such as egg-production traits, body weight characteristics, and intramuscular fat content.…”
Section: Applicationsmentioning
confidence: 99%
“…[62][63][64] With respect to fish and amphibians, species identification and the detection of environmental samples and closely related organisms were recently conducted using PCR-RFLP. [56][57][58][59][60][61][62][63][64][65][66][67][68] The PCR-SSCP was used in the detection of parasite species. 69 The ease of the use of PCR-RFLP was demonstrated in its successful implementation in species identification and discrimination in algae, bacteria, and fungi.…”
Section: Parameter Of Comparison Pcr-rflp Pcr-sscpmentioning
confidence: 99%